Analysis of the Implementation of the Complete Systematic Land Registration Program (PTSL) in Achieving Legal Certainty for Landowners (A Study in the Gayamsari District, Semarang City) - Avio Rieska Berti (Semarang State University Undergraduate Law and Society Review, 2025)
The Complete Systematic Land Registration (PTSL) is a government program that aims to accelerate the land certification process to provide legal certainty for the community. However, in its implementation, PTSL still faces various obstacles, such as a lack of public understanding of registration procedures, costs that are considered burdensome, and challenges in validating land data. Therefore, this study aims to analyze the effectiveness of PTSL implementation and identify factors that influence the success and obstacles in the land certification process. This research uses a qualitative approach with a survey method. Data were collected through questionnaires and interviews with relevant parties and the data were analyzed using descriptive statistics and regression methods to see the relationship between the variables studied. The results show that PTSL has a positive impact in increasing legal certainty over land ownership and accelerating the certification process. However, there are some major obstacles in its implementation. The conclusion of this study is that the success of PTSL is strongly influenced by the effectiveness of socialization, ease of administrative procedures, and more inclusive regulatory support. To improve the effectiveness of this program, it is recommended to simplify the registration process, optimize the role of the government in providing cost subsidies, and increase the capacity of human resources in land management.